2006
DOI: 10.1007/s00737-006-0164-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety and depression during pregnancy in a private setting sample

Abstract: Prevalence of AA and AD were high in this sample of women attending a private care setting, particularly AA state and trace. AA and AD were associated with similar socio-demographic and socio-economic risk factors, suggesting some common environmental stressors may be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
191
6
34

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(248 citation statements)
references
References 35 publications
14
191
6
34
Order By: Relevance
“…As shown in Table 2, 40% were primipara, and 31.2% were in their second pregnancy. Around 11% had a previous obstetric complication, 12.4% and 16.3% reported spontaneous and induced abortions respectively. Preterm birth was reported by 10% of participants.…”
Section: Obstetric Variables and Medical Historymentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 2, 40% were primipara, and 31.2% were in their second pregnancy. Around 11% had a previous obstetric complication, 12.4% and 16.3% reported spontaneous and induced abortions respectively. Preterm birth was reported by 10% of participants.…”
Section: Obstetric Variables and Medical Historymentioning
confidence: 99%
“…a study that reported an antenatal depression prevalence of 37.9%) reported prevalence rates ranging from 13% to 20.8% 4,7,12,14,26,29,37 . The validity of these findings still needs to be established as the majority of these studies focused on pregnant adolescents 4,26,29,37 and women receiving prenatal care in obstetric out-patient clinics in hospital settings 7,12,14,26,29 . These samples are likely to be biased because women with high-risk pregnancies are more likely to seek prenatal care in hospitals.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…[12] The literature has shown that the coping strategies mothers use are linked to the risk of depressive symptoms, with some strategies being more functional than others. [14][15][16][17][18] We have noted, however, that when coping mechanisms are dysfunctional, the perception of stress is exacerbated and a mother's feeling of competency is reduced. [19] Research has also shown that women's perceptions of the social support they have or do not have could equally impact on their stress levels and feelings of competency.…”
Section: Stressmentioning
confidence: 99%